Measuring the Alkylation Kinetics and Drug Likeness of Four Candidate Antineoplastic Compounds - , Ronald Bartzatt (Archives of Current Research International, 2015)
Aims: To synthesize small molecule alkylating compounds and analyze the kinetics of the alkylation in aqueous solution. Determine molecular properties and the drug likeness of these four compounds as potential antineoplastic agents and apply statistical analysis to identify interrelationships of properties. Study Design: Four compounds were synthesized, characterized, and studied for alkylation capability. The alkylation kinetics were elucidated, as well as drug likeness properties. The interrelationships of properties were examined by statistical methodology. Place and Duration of Study: Department of Chemistry, Durham Science Center, University of Nebraska at Omaha, Omaha NE, from May 2015 to June 2015. Methodology: Four compounds were modified by the covalent bonding of an alkyl halide substituent or nitrogen mustard group. The four compounds were placed in aqueous solution at pH 7.4 and 37°C to monitor alkylation efficiency that targeted p-chloroaniline. Alkylation was monitored utilizing fluorescamine and measurement at 400 nm. Time and absorbance plots determined whether alkylation step is first-order or second-order. Molecular properties Log P, formula weight, polar surface area, etc., were determined. Statistical analysis and path analysis revealed which molecular property was most responsible for rate constant values. Results: Compounds A, B, C, and D showed ranges of Log P, formula weight, and polar surface area of 0.010 to 4.21, 177.59 to 714.77, and 29.64 to 88.63, respectively. All compounds showed a favorable drug likeness, with only compound C showing a violation of the Rule of 5. The Log P values and number of alkylation reactive sites were most responsible for rate constant value. Conclusion: Small molecule alkylating agents are synthesized, the efficiency of alkylation measured in aqueous solution utilizing fluorescamine at pH 7.4 and 37°C. Rate-order of reactions is determined utilizing fluorescamine assay for surviving primary amine groups. The four compounds showed a favorable drug likeness based on molecular properties.